Disrupted resting-state interhemispheric functional connectivity in patients with first-episode moyamoya disease - Jiajia Nie; Li Qi; Pan Wu; Chao Li; Baogen Du; Chen Chen; Shanshan Cao; Qiang Wei; Kai Wang; Ling Wei; Yanghua Tian (Scientific Reports)
Abstract Moyamoya disease (MMD) has been reported to be associated with a wide range of structural and functional abnormalities of bilateral hemispheres. However, whether the interhemisphere functional connectivity (FC) of MMD patients is altered and its relationship with cognitive impairments still remain unclear. A total of 20 patients with MMD and 25 healthy subjects were included, matched based on age, sex, and level of education. All participants were given cognitive assessments, and the whole-brain voxel-mirrored homotopic connectivity (VMHC) was derived through rs-fMRI analysis. The study utilized Pearson correlation analysis to examine the relationship between VMHC values and neuropsychological test results. Compared to the healthy controls, patients with MMD exhibited significantly lower VMHC in the middle frontal gyrus (MFG), orbital part of the inferior frontal gyrus (IFGorb), postcentral gyrus (PoCG) and angular gyrus (AG). Furthermore, following Pearson correction, a significant positive correlation was found between the recognition section scores of the Rey Auditory-Verbal Learning Test (AVLT) and the VMHC value for the PoCG and AG in MMD patients. This study is limited by its small sample size and cross-sectional design, which preclude the establishment of causal relationships between imaging indicators and clinical symptoms. These results suggest that VMHC analysis offers valuable insights into potential bilateral brain functional activity in MMD subjects, providing new perspectives on the neuroimaging mechanisms associated with cognitive decline, particularly memory impairment.